Optimizing Gel Formulations Using Carbopol 940 and Sodium Alginate Containing Andrographis paniculata Extract for Burn-Wound Healing - Apriani, Elsa Fitria; Kornelia, Naisa; Amriani, Annisa (Universitas Airlangga, 2023)
Background: Sambiloto leaves (Andrographis paniculata (Burm.f.) Nees) contain andrographolide (diterpene lactone), flavonoids, quinic acid, steroids, saponins, alkaloids, and tannins, which act as anti-inflammatory, antioxidant, antibacterial, and wound healing. Objective: This study optimizes the gelling ingredient in Sambiloto extract gel preparations (Andrographis paniculata (Burm.f.) Ness) as a wound healer in male Wistar rats. The gelling agent is an important component that can affect active substance release. Methods: Formula optimization was developed using the Regular Two-Level 22 Factorial Design method in Design-Expert 12 software. This study used 0.5%-1% carbopol 940 and 1%-5% sodium alginate. Carbopol 940 and Sodium Alginate have different characteristics, so they need to be optimized to produce a gel with good characteristics. Results: Physical property evaluation using factorial design revealed the optimal formula at 0.5% carbopol and 5% sodium alginate, with average pH, viscosity, and adhesion values of 5.17 ± 0.04; 2934.452±286.871 cPs; and 194.236±3.684 s. Centrifugation and cycling tests indicated no organoleptic changes, phase separation, or significant changes in pH. ANOVA analysis showed that the gel with 10% Sambiloto leaf extract had similar burn healing activity to the positive control, with a recovery rate of 99.72 ± 0.47% in 20 days. Scabs formed on the 8th day and peeled off on the 12th day. Conclusion: Sambiloto extract gel in the optimum formula has the potential to be developed as a burn wound-healing drug.